2015
DOI: 10.1021/acsami.5b01167
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coating from Phosphonate Ionic Liquid Electrolyte for the Enhancement of the Tribological Performance of Magnesium Alloy

Abstract: A chronoamperometric method has been applied for the growth of a surface coating on AZ31B magnesium alloy, using the imidazolium alkylphosphonate room-temperature ionic liquid 1-ethyl-3-methylimidazolium ethylphosphonate ([EMIM][EtPO3H]) as electrolyte. A surface coating layer is obtained after 4 h under a constant voltage bias of -0.8 V with respect to the standard electrode. The coating nucleation and growth process correlates well with a 3D progressive mechanism. X-ray photoelectron spectrometry (XPS) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 75 publications
0
10
0
2
Order By: Relevance
“…Controlling friction by lubrication is important in metal forming not only for reducing energy consumption but also for enhancing the surface quality of the formed components and the forming limitations [ 10 ]. Nonetheless, so far few lubricants are exclusively used for the forming process of Mg alloy, and in some cases, the forming lubricants used for Al alloy forming are casually used and the consequences are not favorable.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling friction by lubrication is important in metal forming not only for reducing energy consumption but also for enhancing the surface quality of the formed components and the forming limitations [ 10 ]. Nonetheless, so far few lubricants are exclusively used for the forming process of Mg alloy, and in some cases, the forming lubricants used for Al alloy forming are casually used and the consequences are not favorable.…”
Section: Introductionmentioning
confidence: 99%
“…Recently [7][8][9], the formation of surface films on magnesium alloy by treatment with ionic liquids (ILs) containing P has been studied. Although initial studies confirmed improvement in the corrosion resistance of magnesium alloys due to the formation of a passivating surface film when immersion in phosphonium IL, this surface film used to be heterogeneous and with defects [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of surface science and engineering, ionic liquids have shown outstanding potential as lubricants and lubricant additives [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , even in the friction and wear reduction of highly reactive light alloys [17][18][19][20] , polymers [21][22][23][24][25][26] , and also as nanophase modifiers 23,24 , electrolytes [27][28][29] , corrosion inhibitors [27][28][29][30][31][32][33][34][35][36] or promoters of surface coatings [37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%